PENGARUH GAYA KEPEMIMPINAN KEPALA DESA TERHADAP KINERJA PEGAWAI PADA KANTOR DESA COMPANG SOBA KABUPATEN MANGGARAI TIMUR - Herman Jelatu; Maksimus Agung (Jurnal Humaniora & Sosial Sains, 2024)
This study aims to determine the effect of village head leadership style on employee performance at the Comang Soba Village Office, East Manggarai Regency. The population in this study were 27 employees with a sampling technique using saturated samples, so the sample was 27 village employees. The research method used was quantitative. Data were analyzed using normality tests, multicollinearity, simple linear regression, partial tests and coefficient of determination tests. The results of the normality and multicollinearity tests showed that the data were normally distributed and there was no multicollinearity. Regression analysis showed that there was a positive effect of leadership style on the performance of employees of the Compang Soba village, East Manggarai Regency. The partial test showed that leadership style had a significant effect on the performance of employees of the Compang Soba village, East Manggarai Regency. The coefficient of determination test explained that leadership style was able to influence employee performance by 67.8% and 33.2% was influenced by other variables not examined in this study.